1997
DOI: 10.3109/01612849709009424
|View full text |Cite
|
Sign up to set email alerts
|

Providing Sanctuary for Battered Women: Nicaragua'sCasas De La Mujer

Abstract: A combination of participant observation and in-depth interviews (10 with key informants; 21 with battered women) was used to investigate wife battering in Nicaragua and the casas de la mujer, or women's centers, that have been established to help abused women. The results are presented within the context of the historical and structural realities of women's lives in Nicaragua and the sanctions and sanctuary framework of cultural analysis of wife battering. Nicaraguan wife battering is exacerbated in the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…The empowerment and engagement of FCVs in IPV prevention are consistent with published attempts to promote the establishment of female solidarity groups and support networks in Latin American nations including Mexico (Castro et al 2008; Pick et al 2006) and Nicaragua (Ellsberg et al 2000; Ellsberg et al 2001; Wessel and Campbell 1997). In a comprehensive study spanning ten Latin American nations including Honduras, researchers found that optimal support for IPV victims came from women’s organizations that connected women’s health and legal rights (Sagot 2005).…”
Section: Discussionsupporting
confidence: 75%
“…The empowerment and engagement of FCVs in IPV prevention are consistent with published attempts to promote the establishment of female solidarity groups and support networks in Latin American nations including Mexico (Castro et al 2008; Pick et al 2006) and Nicaragua (Ellsberg et al 2000; Ellsberg et al 2001; Wessel and Campbell 1997). In a comprehensive study spanning ten Latin American nations including Honduras, researchers found that optimal support for IPV victims came from women’s organizations that connected women’s health and legal rights (Sagot 2005).…”
Section: Discussionsupporting
confidence: 75%
“…However, in the past decade, both government and grass roots organisations have attempted to change prevailing attitudes towards violence. Over 100 centres have been set up throughout the country to provide support to battered women or to carry out educational or violence prevention programmes 38. The majority of the centres are run by local women's organisations who coordinate their actions through a broad based coalition called the National Network of Women against Violence.…”
mentioning
confidence: 99%
“…This result may be reflective of the marianismo characteristics that expect women to be submissive in their relationships with men (Brabeck & Guzman, 2009;Marrs Fuchsel et al, 2012). By definition, a woman that is accepting of marianismo would not engage in aggressive tactics as a means of ensuring her partner maintains his reciprocal machismo elevated status (Marrs Fuchsel et al, 2012;Wessel & Campbell, 1997). Thus, the question arises of whether it is a buffer for engagement in psychological aggression or simply reflects their submissiveness in the face of traditional gender role expectations.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, prior research has noted marianismo, machismo and caballerismo gender role frameworks play an important role in Hispanic emerging adults intimate relationship processes (CDC, 2014;Marrs Fuchsel et al, 2012;Wessel & Campbell, 1997). Through the identification of the meanings and perceptions women hold about machismo and caballerismo research can better address the ways in which these masculinity beliefs impact experiences with psychological aggression, specifically, and IPV, broadly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation